2018
DOI: 10.5830/cvja-2018-008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of treatment with atorvastatin versus rosuvastatin on endothelial dysfunction in patients with hyperlipidaemia

Abstract: SummaryIntroductionStatins can reduce cardiovascular events and improve endothelial function. However, differences in the effect of statins on endothelial dysfunction have not been researched sufficiently. Here, we aimed to compare the effects of atorvastatin versus rosuvastatin on endothelial function via flow–mediated and endothelial–independent dilation. MethodsHyperlipidaemic subjects on treatment with statins for one year (either 20 mg/day atorvastatin or 10 mg/day rosuvastatin) were enrolled in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the consequence of impaired endothelium-mediated dilatation in the resistance vessels would be the elevation of SVR. Twelve month treatment with statins improved flow-mediated dilatation in the brachial artery [25], while a meta-analysis reported increased flow-mediated dilatation following treatment with pitavastatin [26].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, the consequence of impaired endothelium-mediated dilatation in the resistance vessels would be the elevation of SVR. Twelve month treatment with statins improved flow-mediated dilatation in the brachial artery [25], while a meta-analysis reported increased flow-mediated dilatation following treatment with pitavastatin [26].…”
Section: Discussionmentioning
confidence: 97%
“…As the deleterious effect of LDL-C on endothelial dysfunction can be reversed by statins, this provides a potential explanation for the beneficial effects of these agents on BP [20,[24][25][26]. Experimental evidence suggests that LDL-C can increase the angiotensin II type 1 receptor density in the arterial wall [15,17], while statin treatment in vivo can reduce the vasoconstrictor responses elicited by angiotensin II in isolated human internal thoracic artery segments in vitro [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both 1-year atorvastatin and rosuvastatin treatments significantly improved endothelial function, when assessed with FMD and measured by ultrasonography. 5 Jafari et al and Jafari and Mohsenin 6,7 reported that there was…”
Section: Introductionmentioning
confidence: 99%
“…Both 1-year atorvastatin and rosuvastatin treatments significantly improved endothelial function, when assessed with FMD and measured by ultrasonography. 5 Jafari et al and Jafari and Mohsenin 6,7 reported that there was a significantly inverse correlation between YKL-40 and FMD in hypertensive obstructive sleep apnea (H-OSA) and obstructive sleep apnea (OSA) patients. 6 Serum pentraxin-3 levels are closely related with the measures of indirect noninvasive evaluation methods (FMD) in both dipper and non-dipper hypertension patients.…”
Section: Introductionmentioning
confidence: 99%